DOI: 10.1159/000421905
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Diversity in Developmental Pathways: Methods and Concepts

Abstract: Pour une integration des methodes en psychologie: Approches experimentale, psycho-genetique et differentielle [For an integration of methods in psychology: experimental, psychogenetic and differential perspectives]. I. '.lt!nCc ~c / i o h c~i~j i n .~. 84. 227-250. de Ribaupierre. A., & Rieben, L. (!985). Etudc du fonctionnemcnt operatoire: Queiques problemes methodologiques [The study of operational functioning: some methodological problems]. Budletin de I?s!~~/iotogie. 38. 84 1-85?,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 19 publications
2
29
0
1
Order By: Relevance
“…This possibility is particularly relevant to the two older groups where more variance in response level was apparent. While this finding is consistent with other research within Case's perspective (Case, 1992), it suggests that tasks whose demand spans multiple levels of development (Fischer, Knight, & Van Parys, 1993) may elicit a more accurate picture of what children in middle childhood think about their own intelligence. It also would be appropriate to have more information on the types of classroom environments and feedback on ability which children experience.…”
Section: Discussionsupporting
confidence: 90%
“…This possibility is particularly relevant to the two older groups where more variance in response level was apparent. While this finding is consistent with other research within Case's perspective (Case, 1992), it suggests that tasks whose demand spans multiple levels of development (Fischer, Knight, & Van Parys, 1993) may elicit a more accurate picture of what children in middle childhood think about their own intelligence. It also would be appropriate to have more information on the types of classroom environments and feedback on ability which children experience.…”
Section: Discussionsupporting
confidence: 90%
“…Her studies found some conceptual advancement in these domains, usually of the order of a substage (approximately two years), combined with considerably more advanced specific language and artistic skills. Early development of narrative is evident in storytelling and interpersonal understanding, supporting findings that show there are multiple pathways to, and demonstration of, giftedness in any one domain (Golomb, 1992;Fischer et al, 1993;Porath, 1993Porath, , 2000Robinson, 1993), as well as complexity within domains. This complexity may result from an integration of significantly advanced skills with conceptual understanding.…”
Section: Giftedness From a Neo-piagetian Perspectivesupporting
confidence: 53%
“…A escola tem o potencial educativo de mobilizar a expressão de zonas proximais do estudante, impulsionando-o a funcionar em nível ótimo (Fischer, Knight, & van Parys, 1993;Kozulin, Gindis, Ageyev, & Miller, 2003;Vygotsky, 1978). Por outro lado, a escola pode mobilizar as práticas pedagógicas de modo a enfatizar o nível funcional do aluno.…”
Section: Discussionunclassified